Адаптація студента першокурсника до навчання в університеті - Болотова, Вікторія Олександрівна; Ляшенко, Наталія Олександрівна (Класичний приватний університет, 2017)
У статті описано основні аспекти соціальної адаптації студента-першокурсника, а саме соціально-психологічний, дидактичний і психофізіологічний. Зазначено фактори адаптації, які можуть сприяти або утруднювати її успішність. Наведено дані соціологічного дослідження, за результатами якого виявлено основні проблеми, що виникають під час первинної адаптації студентів (на прикладі НТУ "ХПІ"), здійснено вимірювання рівня їх адаптованості. Описано основних суб’єктів, від яких студенти отримували допомогу в процесі адаптації.

The article describes social adaptation of the first-year student when enrolling in a university, primary and secondary stages were especially highlighted. The authors examined the main aspects of the student’s primary social adaptation, namely them as sociopsychological, didactic and psychophysiological aspects. Socio-psychological aspect is associated with the disruption of some previous social relations and with the need of creation of new relations with other students in the study group, with the roommates and teachers. The didactic aspect of adaptation is related to adaptation to new requirements and knowledge control forms, of the organization of the study process, which is differ from the school in providing much more autonomy. Psychophysiological aspect is associated with the adaptation to new conditions and rhythm of life, an independent solution of domestic problems. The authors name the internal and external factors of student adaptation, which contribute to its acceleration or complicate the process. The first factor reflects the state of readiness of the student to a new knowledge (the volume and the level of knowledge student received before enrolling to university, professional orientation of enrollee, interest in study activities in general and interest to their profession, state of the health, independence of the choice of profession) and psychological characteristics of the person, which help to overcome the difficulties and create new social relationships to the new environment (persistence, responsibility, independence, sociability, politeness, willpower). The second factor consists of the conditions for studying and living, and "factors of accompanying a first-year student by the university". It is stated that the factors of the second group can be quickly adjusted to facilitate and accelerate first-year student adaptation. The materials of a specific sociological study of the National Technical University "Kharkov Polytechnic Institute" revealed the main problems which arise during their primary didactic, psychophysiological and socio-psychological adaptation, determined severity and indicators of the first-year students’ adaptation after the first six months of study. The authors determined the level of didactic adaptation, the indicators of which were the ability to note lectures, find the necessary educational literature, and fulfill the homework. It was proved that social and psychological adaptation was successful for majority of students, and psychophysiological and didactic ones were successful only for the half of them. The authors carried out a comparative analysis of the level of adaptation of technical, chemical, IT, economic and humanitarian students, compared those who study on government payment and on private one. Particular attention was paid to the adaptation of out-of-town students. It was revealed from whom the young men and women received help and whom they addressed the problems which arose during the initial adaptation. It was revealed imagination of students about the duties of the group’s curator and their evaluation of curators’ activities.
Adapting of the First-Year Student to Study at University
Keywords: соціалізація; соціальна адаптація; первинна адаптація студентів; навчальний процес; студентство; педагогічна діяльність; socialization; social adaptation; primary student adaptation